1997
DOI: 10.2307/3802428
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effects of Survival and Reproduction on the Population Dynamics of Emperor Geese

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 31 publications
4
49
0
Order By: Relevance
“…Also, Harlequin Duck adult female survival during winters 1995-1998 was lower on oiled areas than unoiled areas , and laboratory studies support logical links between reduced survival rates and oil exposure (Holmes et al 1979). Because population dynamics of birds with life histories like Harlequin Ducks are particularly sensitive to variation in adult female survival (Goudie et al 1994, Schmutz et al 1997, lower survival on oiled areas may have led to population declines (Rosenberg and Petrula 1998) and hence lower densities on oiled areas than predicted, as found in this study. Harlequin Duck populations have relatively low intrinsic growth rates (Goudie et al 1994), so full recovery (i.e., duck densities at levels predicted from intrinsic habitat attributes) likely will not occur until long after deleterious effects of the oil spill have ceased.…”
Section: Effects Of History Of Oil Contaminationsupporting
confidence: 66%
“…Also, Harlequin Duck adult female survival during winters 1995-1998 was lower on oiled areas than unoiled areas , and laboratory studies support logical links between reduced survival rates and oil exposure (Holmes et al 1979). Because population dynamics of birds with life histories like Harlequin Ducks are particularly sensitive to variation in adult female survival (Goudie et al 1994, Schmutz et al 1997, lower survival on oiled areas may have led to population declines (Rosenberg and Petrula 1998) and hence lower densities on oiled areas than predicted, as found in this study. Harlequin Duck populations have relatively low intrinsic growth rates (Goudie et al 1994), so full recovery (i.e., duck densities at levels predicted from intrinsic habitat attributes) likely will not occur until long after deleterious effects of the oil spill have ceased.…”
Section: Effects Of History Of Oil Contaminationsupporting
confidence: 66%
“…Both methods provide only a moderate degree of relief, at best. Many studies have demonstrated that altering survival of adult geese is much more effective in changing population size than altering recruitment rates (Trost et al 1986;Schmutz et al 1997). However, direct culling of molting birds continues to remain a socially unacceptable option for population control in many areas.…”
mentioning
confidence: 99%
“…In long‐lived bird species like geese, population growth rate is more sensitive to changes in adult survival than in fecundity (Lebreton & Clobert 1991, Schmutz et al . 1997, Tombre et al .…”
mentioning
confidence: 99%